Pengaruh Infrastruktur Transportasi terhadap Pertumbuhan Ekonomi Regional: (Studi pada Provinsi-Provinsi di Pulau Sumatera) - Murbanto Sinaga (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of road, port, and airport infrastructure on regional economic growth in Sumatera Island. Using secondary data and a quantitative analytical approach, the research examines the relationship between three types of transportation infrastructure and regional economic growth. The study was conducted across 10 provinces on Sumatera Island, with data obtained from the official website of Statistics Indonesia (Badan Pusat Statistik/BPS) accessed online. Data were analyzed using multiple linear regression. The findings reveal that road infrastructure has a positive and significant effect on economic growth. Port infrastructure is also proven to have a positive and significant impact on economic growth. Conversely, airport infrastructure shows a negative but insignificant effect on economic growth. Meanwhile, the simultaneous test indicates that road, port, and airport infrastructure collectively have a significant influence on regional economic growth in Sumatera Island. This study provides important implications for regional development policy. The government needs to prioritize strengthening road and port infrastructure to enhance logistics efficiency, reduce distribution costs, and improve interregional accessibility. The development of airport infrastructure remains necessary but should be directed toward improving cargo services and integrating airport facilities with industrial zones to generate a more optimal economic contribution..